FACTORS AFFECTING THICKENING OF CAROTID INTIMA MEDIA THICKNESS IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Yonata, Ade; Ali, Zulkhair; Indrajaya, Taufik; Effendi, Ian; Suhaimi, Novadian (Biomedical Journal of Indonesia, 2020)
Chronic kidney disease (CKD) is associated with high mortality rates related to cardiovascular complications. Atherosclerosis, arteriosclerosis and vascular calcification conditions are often found in CKD patients. Carotid intima media thickness (cIMT) thickening is one of the parameters of vascular disorders. A cross sectional study was conducted on patients with chronic kidney disease in the hospital. Mohammad Hoesin Palembang. Patients' blood samples were examined in the hospital laboratory. CIMT thickening was examined using echocardiography. A total of 55 patients with stage 3-5 chronic kidney disease were examined. The median cIMT is 0.8 (0.6-1.45) mm. Spearman's correlation analysis showed a significant correlation between triglyceride levels and thickening of cIMT (r = 0.303, p = 0.025). A significant correlation was also shown between phosphate levels and cIMT thickening (r = 0.290, p = 0.032). There is a significant correlation of triglyceride levels and phosphate levels to cIMT thickening in patients with chronic kidney disease in Palembang